IMPLEMENTATION OF A REAL-TIME ALERT-NOTIFICATIONSYSTEM FOR DATA MONITORING IN THE FINANCIAL INDUSTRY - Amankossova, Aruzhan; Turan, Cemil (Journal of Emerging Technologies and Computing, 2023)
An alert notification system that operates in real-time is crucial for data monitoring, as it enables financial institutions to detect and address possible compliance issues promptly, preventing them from escalating into more significant problems. In the event that there are issues with the data, we may not realise that some parameter values are missing. In such instances, automatic alerts are unquestionably the most effective system. The use of an automated system to notify the responsible parties will benefit any organization's digitalization and reduce the burden on employees who must monitor manually.The article provides an examination and contrast of real-time alert automation techniques implemented through the programming languages of R and Python.The analysis encompasses the problems and limitations of the different methods.This study contributes to the field of automated notifications in the financial industry by evaluating different methods.